Genetic Diversity of Astrovirus in Children From a Birth Cohort in Nepal - Shrestha, Sanjaya Kumar; Shrestha, Jasmin; Andreassen, Ashild K.; Strand, Tor A.; Dudman, Susanne; Dembinski, Jennifer L. (Frontiers in Microbiology, 2021)
Objective: This study describes the classical and novel Astroviruses in stool samples collected from a birth cohort in Nepal. Methods: We screened 5224 diarrhoeal and non-diarrhoeal stool samples for Astrovirus by ELISA using a commercial kit (ProSpecT). Positive samples (2.8 %) were further analyzed using RT-PCR. The primary RT-PCR assay used targets the ORF2 region and detects Astrovirus type 1-8. Samples that were negative in this assay were further analyzed using primers that target the ORF1b region and can detect both classical and non-classical novel HAstV (MLB1-5, VA 1-5) types. PCR positive samples were analyzed by Sanger sequencing to determine the genotype. Results: A total of 148 available ELISA positive stool samples were analyzed by RT-PCR and further genotyped. RT-PCR analysis of these samples using the ORF2 and ORF1b assay revealed that 124 (84%) were positive for classical Astrovirus type 1-8. Seven different genotypes of classical human Astrovirus were identified (HAstV 1- HAstV 8) with HAstV 5 as the most frequent genotype (42.2%), followed by HAstV 1 (34.7%), HAstV 2 and HAstV 8 (7.4%), HAstV 4 (4.1%), HAstV 3 (3.3%) and HAstV 6 (0.8%). Conclusion: A high diversity of circulating Astrovirus strains were detected in young children, both with and without symptoms of gastroenteritis. HAstV 5 and HAstV 1 were the most common genotypes in young children in Nepal.